2017
DOI: 10.1007/s10461-017-1821-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Financial Incentives Along the Antiretroviral Therapy Adherence Continuum: A Qualitative Sub-study of the HPTN 065 (TLC-Plus) Study

Abstract: The stages of change (SOC) theory suggests individuals adapt incrementally to behaviors like adherence, requiring different strategies over the behavior change continuum. Offering financial incentives (FIs) is one strategy to motivate adherence. This qualitative sub-study examined adherence barriers and the role of FIs to increase viral suppression (VS) among HIV Prevention Trials Network (HPTN) 065 study participants categorized into SOC-related adherence stages based on changes from baseline to follow-up vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The structural barriers including long distances between where people live and where services are and transportation needs to visit the clinics were also mentioned by some key informants. This could be addressed by some stipends for transportation, 18 conditional small cash programs and incentives for those who made their clinic visits on time, 19 which not only improves adherence, but also encourages marginalized populations with low incomes to visit the services more often. 19 Perceived or real stigma has also been reported as one of the barriers for HIV testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural barriers including long distances between where people live and where services are and transportation needs to visit the clinics were also mentioned by some key informants. This could be addressed by some stipends for transportation, 18 conditional small cash programs and incentives for those who made their clinic visits on time, 19 which not only improves adherence, but also encourages marginalized populations with low incomes to visit the services more often. 19 Perceived or real stigma has also been reported as one of the barriers for HIV testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This could be addressed by some stipends for transportation 18 , conditional small cash programs and incentives for those who made their clinic visits on time 19 , which not only improves adherence, but also encourages marginalized population with low income to visit more often the services. 19 Perceived or real stigma has also been reported as one of the barriers for HIV testing and treatment. Educating communities and patients for their rights 20 , normalizing HIV testing by campaigns 21 and by wisely involving partners and families as supporting groups 14 can reduce the stigma associated with HIV and increase the chance of using the existing services.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative findings from a U.S.-based RCT sub-study found that CCTs were particularly motivating for moderate adherers at baseline (Tolley et al, 2016). A final experimental study in the Democratic Republic of the Congo found that CCTs given to HIV-positive pregnant women supported retention throughout the PMTCT cascade (Yotebieng et al, 2016).…”
Section: Provision Interventionsmentioning
confidence: 99%
“…Reasons for persistence of benefits may be gleaned from qualitative work conducted among staff and patients at sites randomized to FI in HPTN 065. 27,28 In interviews with recipients of FI and staff involved in the intervention at those sites, the incentives were widely welcomed and associated with strong bidirectional emotional benefits, ie, for both the providers and recipients of care. The durability of significant effect of FI on continuity in care demonstrates deeper engagement of patients with their providers and offers an opportunity to garner benefits from ongoing contact with their providers.…”
Section: Discussionmentioning
confidence: 99%